A perspective on global access to insulin: a descriptive study of the market, trade flows and prices. Issue 6 (7th April 2019) - Beran, D.; Laing, R. O.; Kaplan, W.; Knox, R.; Sharma, A.; Wirtz, V. J.; Frye, J.; Ewen, M.
Abstract: Aim: To describe the global insulin market. Methods: Market intelligence data, United Nations Commodity Trade Statistics for insulin trade, the International Medical Products Price Guide for prices of human insulin and additional web searches were used as data sources. These sources were combined to gain further insight into possible links among market, trade flows and prices. Descriptive statistics and Spearman's rank order correlation were used for the analysis. Results: A total of 34 insulin manufacturers were identified. Most countries and territories are reliant on a limited number of supplying countries. The overall median (interquartile range) government procurement price for a 10‐ml, 100‐IU/ml vial during the period 1996–2013 equivalent was US$4.3 (US$ 3.8–4.8), with median prices in Africa (US$ 4.7) and low‐ (US$ 6.9) and low‐ to middle‐ (US$ 4.7) income countries being higher over this period. The relationships between price and quantity of insulin (Spearman's r =0.046; P >0.1) and number of import links (Spearman's r =0.032; P >0.1) were weak. The links between price and percentage of total insulin from a country where a 'big three' manufacturer produces insulin (Spearman's r =0.294; P <0.05) and total insulin from the main import link (Spearman's r =–0.392; P <0.05) were stronger. Conclusions: This research shows the high variability of insulin prices and the reliance on a few sources, both companies and countries, for global supply. In addressing access to insulin, countries need to use existing price data to negotiate prices, and mechanisms need to be developed to foster competition and security of supply of insulin, given the limited number of truly global producers. What's new?: Very little is known about the global insulin market and its possible impact on access to insulin in a given country. Current evidence, using traditional methodological approaches, suggests poor availability and affordability of insulin in specific contexts. Insight is provided into the insulin market in terms of numbers of insulin‐producing companies, trade flows of insulin, global prices of insulin and the possible impact of different factors on the price of insulin for individual countries. This study uses data sources traditionally not used in health research and offers a perspective on how to gain a better understanding of the global pharmaceutical market and access to medicines.